Early stages of unwinding of zwitterionic alpha-helical homopolymeric peptides - Pandey, Prithvi Raj; Roy, Sudip (Chemical Physics Letters, 2011)
Unwinding mechanisms of helices of the zwitterionic polyalanine, polyleucine, and polylysine were studied using classical molecular dynamics simulation at 300 K temperature. Interestingly the helices of polyalanine and polyleucine start to unwind from the terminals, which is further relayed to the middle of the chain with time. Polylysine helix also starts to unwind from the terminals of the alpha-helical chain but the unwinding is not relayed to the middle. The reason behind this observation is investigated whether the presence of -NH(2) groups in the side chain of polylysine is influencing the unwinding. Two competitive mechanisms, fluctuation of the terminal residues and exchange of H-bonds between residues and water trigger the process of unwinding. (C) 2011 Elsevier B. V. All rights reserved.

Headgroup mediated water insertion into the DPPC billayer: a molecular dynamics study - Pandey, Prithvi Raj; Roy, Sudip (Journal of Physical Chemistry B, 2011)
Molecular dynamics simulation was performed on the 1,2-dipalmitoyl-sn-phosphocholine (DPPC) bilayer-water system using the GROMOS96 53a6 united atom force field. The transferability of force field was tested by reproducing the area per lipid within 3% accuracy from the experimental value. The simulation shows that water can penetrate much deeper inside the bilayer almost up to the starting point of the aliphatic chain. There is significant evidence from experiments that water goes deep in the DPPC bilayer, but it has not been reported from theoretical work. The mechanism of insertion of water deep inside the lipid bilayer is still not clear. In this report, for the first time the mechanism of water insertion deep into the bilayer has been proposed. Water transport occurs by the headgroup and its first solvation shell. The trimethyl ammonium (NMe3) group (headgroup of DPPC) has two stable conformations at the bilayer-water interface, one outside the bilayer and another inside it. The NMe3 group has a large clustering of water around it and takes the water molecules inside the bilayer with it during its entry into the bilayer. The water molecules penetrate into the bilayer with the help of the NMe3 group present at the headgroup of DPPC and eventually form hydrogen bonds with carbonyl oxygen present deep inside the bilayer. Structural characteristics at the bilayer-water interface region are also reported.

Distinctions in early stage unwinding mechanisms of zwitterionic, capped, and neutral forms of different alpha-helical homopolymeric peptides - Pandey, Prithvi Raj; Roy, Sudip (Journal of Physical Chemistry B, 2012)
Molecular dynamics simulations of alpha-helical polyalanine, polyleucine, polylysine, and poly(glutamic acid) with different forms of terminal groups in water at 300 K showed sharp distinctions in their unwinding mechanisms. Zwitterionic, capped, and neutral forms of polyalanine, polyleucine, and polylysine have been explored to elucidate their unwinding mechanism at very early stage, e.g., initial time window. Role of water in the unwinding mechanisms of the various helices has been envisaged. Also, it is evident from our calculations that the short- and long-range nonbonded interactions among the side chains is an important factor determining the unwinding mechanisms of the various homopolymeric alpha-helices. These findings can be helpful in constructing predictive models for understanding of the unwinding of alpha-helical proteins and peptides.

Molecular dynamics simulation of phosphoric acid doped monomer of polybenzimidazole: a potential component polymer electrolyte membrane of fuel cell - Pahari, Swagata; Choudhury, Chandan Kumar; Pandey, Prithvi Raj; More, Minal; Venkatnathan, Arun; Roy, Sudip (Journal of Physical Chemistry B, 2012)
Phosphoric acid doped polybenzimidazole is promising electrolyte membranes for high temperature (100 degrees C and above) fuel cells. Proton conduction is governed by the amount of phosphoric acid content in the polymer membrane. In this present work, we perform molecular dynamics simulations on phosphoric acid doped 2-phenyl-1H,1'H-5,5'-bibenzo[d]imidazole (monomer unit of polybenzimidazole) to characterize the structural and dynamical properties at varying phosphoric acid content and temperature. From the structural analysis, we have predicted the arrangement of the phosphoric acids, formation of H-bonds in the system, and the contribution of different atoms toward H-bonding. We have also examined the stacking of 2-phenyl-1H,1'H-5,5'-bibenzo[d]imidazole molecules and how their arrangement changes with the increasing amount of PA in the system with the help of cluster analysis. From the molecular dynamics simulation conducted at different temperatures and phosphoric acid doping level, we have predicted the diffusion of phosphoric acid and monomer. As a dynamic quantity, we have also calculated ring flipping of the imidazole ring of the monomer.

Is it possible to change wettability of hydrophilic surface by changing its roughness? - Pandey, Prithvi Raj; Roy, Sudip (Journal of Physical Chemistry Letters, 2013)
Wetting behavior of model rough surfaces made of hydrophilic square pillars is investigated. The hydrophilic pillars are equally spaced on hydrophilic surface. The surface roughnesses are altered by varying the pillar width and interpillar spacing. Wetting to dewetting transition is observed for these surfaces. This is one of the first accounts of observation from molecular simulations where hydrophilic surface converts into hydrophobic by changing its roughness. The extent of hydrophilicities are also changed to gain more insightful observations. Energies of the wetting to dewetting transitions are analyzed by calculating the contribution from water water and water surface energy components. A correlation between energy and the wetting to dewetting transition has been established, which rationally explains the observed water repellent nature of hydrophilic surface as a function of roughness.

Model atomistic protrusions favouring the ordering and retention of water - Pandey, Prithvi Raj; Roy, Sudip (Physical Chemistry Chemical Physics, 2014)
The ordering of water molecules near model linear atomistic protrusions is studied using classical molecular dynamics simulations. The protrusions are made up of Lennard-Jones particles of hydrophobic and hydrophilic blocks. Simulations are performed at a range of temperatures and pressures, keeping the position of the protrusions fixed. At different temperatures and pressures, the ordering and residence time of water molecules is enhanced on the surface of the hydrophilic block. Detailed analysis of the systems shows that the surface region is potentially the most energetically favorable for water molecules, which is consistent with the tetrahedral ordering of water molecules. A competition between energetics and structuring is observed from residence time calculations.

Vesicle structures from bolaamphiphilic biosurfactants: experimental and molecular dynamics simulation studies on the effect of unsaturation on sophorolipid self-assemblies - Dhasaiyan, Prabhu; Pandey, Prithvi Raj; Visaveliya, Nikunjkumar; Roy, Sudip; Bhagavatula L. V. Prasad (Chemistry-A European Journal, 2014)
The formation of giant-vesicle-like structures by self-assembling linolenic acid sophorolipid (LNSL) molecules is revealed. Sophorolipids belong to the class of bolaamphiphilic glycolipid biosurfactants. Interestingly, the number of double bonds present in the hydrophobic core of sophorolipids is seen to have a great influence on the type of self-assembled structures formed. Dye encapsulation results establish the presence of an aqueous compartment inside the LNSL vesicles. Molecular dynamics simulation (MD) studies suggest the existence of two possible conformations of LNSLs inside the self-assembled structures and that LNSL molecules arrange in layered structures.
Keywords: bolaamphiphiles; MD simulations; Self-assembly; sophorolipids; vesicles

Propensity of self-assembled leucine-lysine diblock copolymeric alpha-helical peptides to remain in parallel and antiparallel alignments in water - Sarkar, Sujit; Pandey, Prithvi Raj; Roy, Sudip (Journal of Physical Chemistry B, 2015)
Molecular dynamics Simulation study of alpha-helical diblock copolypeptides: preassembled in parallel and antiparallel alignments in water are presented. The assembled peptide lamellar structures were not disrupted even: after performing three step simulation protocols. Primarily hydrogen bonds between peptide are responsible for the stability: The analysis of the trajectory also suggests that Water plays a significant role in favoring self assembly We have detected continuous hydrogen bonded network structure, which is further responsible for the stability Of the lamellar structures. We have performed a detailed analysis of the hydrogen bonded network structure and its length. Further, free energy calculations revealed that the degree of stability for both lamellae are similar. The present study provides structural insight into the stability of self-assembled structures of block copolypeptides.

Structural insight into self assembly of sophorolipids: a molecular dynamics simulation study - Pandey, Prithvi Raj; Dhasaiyan, Prabhu; Bhagavatula L. V. Prasad; Roy, Sudip (Zeitschrift Fur Physikalische Chemie-International Journal of Research in Physical Chemistry & Chemical Physics, 2016)
Sophorolipids contain hydrophilic head groups at the ends of a long hydrophobic tail. As a result, sophorolipids can self assemble into variety of structures in water. Atomistic self assembly simulations of sophorolipids are performed in water. Two sophorolipids, oleic acid sophorolipid and linolenic acid sophorolipid, differing in number of double bonds in the hydrophobic tail are considered for this study. Long time self assembly simulations are performed considering 1 :3 lipid to water ratio by weight for both oleic and linolenic acid sophorolipids. In addition to 1 : 3 ratio, long time self assembly simulations are also performed with 1 : 1 and 1 : 2 ratios for linolenic acid sophorolipids. Distinctions in structural arrangements of sophorolipid molecules in the self assembled configuration for all the systems are investigated. The present study aims to provide structural insight into the different self assembled configurations of sophorolipids in water.
Keywords: MD Simulation; self assembly; sophorolipids; United Atom Force Field

Transferability of different classical force fields for right and left handed alpha-helices constructed from enantiomeric amino acids - Biswas, Santu; Sarkar, Sujit; Pandey, Prithvi Raj; Roy, Sudip (Physical Chemistry Chemical Physics, 2016)
Amino acids can form D and L enantiomers, of which the L enantiomer is abundant in nature. The naturally occurring L enantiomer has a greater preference for a right handed helical conformation, and the D enantiomer for a left handed helical conformation. The other conformations, that is, left handed helical conformations of the L enantiomers and right handed helical conformations of the D enantiomers, are not common. The energetic differences between left and right handed alpha helical peptide chains constructed from enantiomeric amino acids are investigated using quantum chemical calculations (using the M06/6-311g(d,p) level of theory). Further, the performances of commonly used biomolecular force fields (OPLS/AA, CHARMM27/CMAP and AMBER) to represent the different helical conformations (left and right handed) constructed from enantiomeric (D and L) amino acids are evaluated. 5- and 10-mer chains from D and L enantiomers of alanine, leucine, lysine, and glutamic acid, in right and left handed helical conformations, are considered in the study. Thus, in total, 32 a-helical polypeptides (4 amino acids x 4 conformations of 5-mer and 10-mer) are studied. Conclusions, with regards to the performance of the force fields, are derived keeping the quantum optimized geometry as the benchmark, and on the basis of phi and psi angle calculations, hydrogen bond analysis, and different long range helical order parameters.

Effect of shape of protrusions and roughness on the hydrophilicity of a surface - Chowdhury, Sheelan Sengupta; Pandey, Prithvi Raj; Kumar, Rajnish; Roy, Sudip (Chemical Physics Letters, 2017)
We have investigated wetting of model rough surfaces made up of hydrophilic triangular and hexagonal pillars (protrusions). The surface roughnesses are altered by varying the area of the rough surface, the height of the pillars, and the surface interactions to the water. We have established a correlation between structure i.e., the shape of a pillar, which actually depends on the number of edges (due to shape), and the wetting phenomena. We have found that surface with higher number of edges repels water at lower roughness value. We explain the correlation by analyzing the variation of interactions energy components and density profiles of water on the structured surfaces. (C) 2017 Elsevier B.V. All rights reserved.